2020
DOI: 10.3390/agronomy10071012
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties and Agro-Morphological Traits for Improved Lodging Resistance in Ethiopian Teff (Eragrostis tef (Zucc.) Trottor) Accessions

Abstract: Susceptibility to lodging is a major constraint on teff production in Ethiopia, but efforts to develop lodging-resistant cultivars have not been successful. We studied the mechanical properties of teff culms and associated agro-morphological traits in field experiments with 320 teff accessions at two sites in northwestern Ethiopia during the 2018 and 2019 growing seasons. The results showed significant variability in both mechanical properties and agro-morphological traits among accessions. Traits contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Recently, we reported that lower seedling density reduces lodging index [21]. Published studies on tef [20,29] and other cereals [28] have shown an association between lower plant height and reduced lodging. Both seedling density and plant height were reduced by the deeper sowing in the field (Table 5).…”
Section: Effect Of Sowing Depth On Lodging and Related Traitsmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, we reported that lower seedling density reduces lodging index [21]. Published studies on tef [20,29] and other cereals [28] have shown an association between lower plant height and reduced lodging. Both seedling density and plant height were reduced by the deeper sowing in the field (Table 5).…”
Section: Effect Of Sowing Depth On Lodging and Related Traitsmentioning
confidence: 90%
“…Plant lodging, defined as the permanent displacement of the stem from the vertical, which is caused by environmental conditions as well as morphological plant traits [17], is the most significant yield-reducing problem in tef, accounting for up to 35% of yield losses [18,19]. While certain studies relate tef lodging to stem characteristics (stem lodging) [20], others [18], including our recently published paper [21], point to shoot-root junction traits (root lodging) as major contributors to tef lodging. In wheat, deeper sowing has been shown to induce a longer, deeper root crown, thus improving plant anchorage and reducing root lodging [17] (and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to stem bending lodging is the type conferred by SD‐1 mutation in rice (Hirano et al ., 2017b). Under field conditions, lodging in tef is typically measured following the method of Caldicott and Nuttall (1979), but various methods have been described both for field and greenhouse‐grown plants (Bayable et al ., 2020; Ben‐Zeev et al ., 2020; Blösch et al ., 2020; Van Delden et al ., 2010). Since our study was based on potted plants in the greenhouse, we used lodging indices that measured the degree of leaning on a 1–9 rating based on USDA‐GRINS descriptors used for tef and also through time course image analysis using PlantCV functions (Gehan et al ., 2017) that considered changes in plant shape based on height to width ratio over time.…”
Section: Discussionmentioning
confidence: 99%
“…Tef’s morphological characteristics including plant height, lengths of the panicle, the peduncle, the internodes (culm length), thickness of the basal internodes, angle of the panicle, tiller number, root characteristics and the relationship of these plant parts with each other are known to influence the degree of lodging in tef (Bayable et al ., 2020; Blösch et al ., 2020; Girma, 2019; Ketema, 1983; Van Delden et al ., 2010), besides environmental conditions and agronomic practices (Ben‐Zeev et al ., 2020; Merchuk‐Ovnat et al ., 2020). The reduction in culm length and increased thickness of the first and second basal internodes are likely factors for the increased lodging resistance observed for the sd‐1 tef lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation